HUBUNGAN PSYCHOLOGICAL WELL-BEING TERHADAP PARASOCIAL RELATIONSHIP PADA INDIVIDU DEWASA AWAL - Muhammad Firliansyah Maliki; Rita Markus Idulfilastri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The increasing engagement of young adults with influencers on social media has increased the likelihood of developing parasocial relationships, defined as one-sided emotional closeness perceived as meaningful by followers toward media figures. Unlike previous studies that have primarily focused on celebrity worship or extreme attachment in fandom contexts, this study examines non-extreme parasocial relationships among influencer followers and distinguishes the roles of overall psychological well-being scores and its dimensions. This study aims to examine the relationship between psychological well-being and parasocial relationships among young adults who follow influencers on social media. A quantitative correlational design was employed involving 371 individuals aged 18–24 years who actively used social media and followed at least one influencer on Instagram, TikTok, or YouTube. Data were collected online using the Psychological Well-Being Short Scale and the Parasocial Relationship in Social Media (PRISM) Survey, and were analyzed using Spearman’s correlation. The results showed that the overall psychological well-being score was not significantly correlated with parasocial relationships; however, several dimensions showed significant positive and negative associations. Specifically, self-acceptance, autonomy, and environmental mastery were positively correlated, whereas purpose in life and personal growth were negatively correlated. These findings indicate that the relationship between psychological well-being and parasocial relationships among young adults is multidimensional. The implication is that research on parasocial relationships should examine the dimensions of psychological well-being separately, rather than relying solely on the total score. ABSTRAK Meningkatnya keterlibatan dewasa awal dengan influencer di media sosial memperbesar peluang terbentuknya parasocial relationship, yaitu kedekatan satu arah yang dirasakan bermakna oleh pengikut terhadap figur media. Berbeda dari penelitian sebelumnya yang lebih banyak berfokus pada celebrity worship atau keterikatan ekstrem dalam konteks fandom, penelitian ini menelaah parasocial relationship non-ekstrem pada pengikut influencer serta membedakan peran skor total dan dimensi-dimensi psychological well-being. Penelitian ini bertujuan untuk menguji hubungan antara psychological well-being dan parasocial relationship pada individu dewasa awal yang mengikuti influencer di media sosial. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional pada 371 individu berusia 18–24 tahun yang aktif menggunakan media sosial dan mengikuti minimal satu influencer di Instagram, TikTok, atau YouTube. Data dikumpulkan secara daring menggunakan Psychological Well-Being Short Scale dan Parasocial Relationship in Social Media (PRISM) Survey, kemudian dianalisis menggunakan korelasi Spearman. Hasil penelitian menunjukkan bahwa skor total psychological well-being tidak berkorelasi signifikan dengan parasocial relationship, tetapi beberapa dimensinya menunjukkan hubungan signifikan, baik positif maupun negatif. Secara khusus, penerimaan diri, kemandirian, dan penguasaan lingkungan berkorelasi positif, sedangkan tujuan hidup dan pertumbuhan pribadi berkorelasi negatif. Temuan ini menunjukkan bahwa hubungan antara psychological well-being dan parasocial relationship pada dewasa awal bersifat multidimensional. Implikasinya, penelitian parasocial relationship perlu menganalisis dimensi psychological well-being secara terpisah, bukan hanya menggunakan skor total.